Russian architectural heritage in China: Yimanpo Station - Glatolenkova, Ekaterina; Bazilevich, Mikhail (project baikal, 2025)
This article examines the historical development of the railway station area at Yimanpo Station, which emerged at the turn of the 19th and 20th centuries during the construction of the Chinese Eastern Railway. Previously unknown archival station plans are published, and the current state and use of the surviving buildings are analyzed in the context of urban development.